Pulmonary therapy (Springer, 2015)
"The journal is dedicated to the publication of high-quality preclinical, clinical (all phases), observational, real-world, and health outcomes research around the discovery, development, and use of pulmonary therapies. Studies relating to diagnosis, pharmacoeconomics, public health, quality of life, as well as patient care, management, and education are also encouraged"--Description (viewed November 22, 2017)